Lifestyle Influences Changes in Fibrin Clot Properties Over a 10-Year Period on a Population Level - Swanepoel, Albe Carina; de Lange-Loots, Zelda; Cockeran, Marike; Pieters, Marlien (Thrombosis and Haemostasis, 2021)
Case–control and observational studies have provided a plausible mechanistic link between clot structure and thrombosis. We aimed to identify lifestyle, demographic, biochemical, and genetic factors that influence changes in total fibrinogen concentration and clot properties over a 10-year period in 2,010 black South Africans. Clot properties were assessed with turbidimetry and included lag time, slope, maximum absorbance, and clot lysis time. Linear mixed models with restricted maximum likelihood were used to determine whether (1) outcome variables changed over the 10-year period; (2) demographic and lifestyle variables, biochemical variables, and fibrinogen single-nucleotide polymorphisms influenced the change in outcome variables over the 10-year period; and (3) there was an interaction between the exposures and time in predicting the outcomes. A procoagulant risk score was furthermore created, and multinomial logistic regression was used to determine the exposures that were associated with the different risk score categories. In this population setting, female gender, obesity, poor glycemic control, increased low-density lipoprotein cholesterol, and decreased high-density lipoprotein cholesterol contributed to the enhanced progression to prothrombotic clot properties with increasing age. Alcohol consumption on the other hand, offered a protective effect. The above evidence suggest that the appropriate lifestyle changes can improve fibrin clot properties on a population level, decreasing cardiovascular disease risk and thus alleviate the strain on the medical health care system.
Keywords: fibrinogen; γ' fibrinogen; fibrin clot properties; epidemiology; lifestyle